Pengaruh Gaya Kepemimpinan Transformasional Dan Transaksional Terhadap Kinerja Tenaga Kependidikan Di Universitas Kapuas Sintang - Florensius Tijan; Nikolas Fajar Wuryaningrat; Neuneung Ratna Hayati (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Higher education plays a crucial role in producing competent human resources and improving workforce skills. To meet these expectations, all aspects of university operations, including administration, must run smoothly. However, there are issues related to the service and discipline of administrative staff, indicating unsatisfactory performance. This could be due to the inappropriate leadership style used. Therefore, this study aims to analyze the influence of transformational and transactional leadership styles on employee performance. The type of research used in this study is quantitative (deductive). This study used questionnaires distributed to 34 educational staff in the administrative and student services departments at Kapuas Sintang University. Transformational and transactional leadership styles were measured using the MLQ (Multifactor Leadership Questionnaire) instrument. Data analysis in this study used the Partial Least Squares (PLS) method. This study proves that Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Contingent Reward have a positive effect on employee performance. On the other hand, Individual Consideration and Management by Exception have no effect on employee performance.